The Reproductive Biology of Rock Ptarmigan (Lagopus mutus) in the Central Canadian Arctic - Cotter, Richard C. (ARCTIC, 1999)
This paper reports on the nesting phenology, breeding biology, and attrition rates at different stages of the breeding cycle of a population of rock ptarmigan (Lagopus mutus) at Windy Lake, Northwest Territories, from 1987 to 1989. By early May, males were on the study area, mostly in flocks numbering in the tens and hundreds. Females arrived two to three weeks later, about one week after males had dispersed and established territories. All males succeeded in establishing a territory, but only 83% were successful in attracting a mate. There were no unmated females. All but one male were monogamous. The initiation of laying was highly synchronous both within and between years, beginning shortly after ground snow cover receded below 50% (early June). Initiation of laying and clutch size were not correlated with either pre-incubation body weight or wing chord of females. The majority (71%) of hens that deserted or had their first nest depredated during laying renested. However, renesting was rare once incubation had commenced. Clutch size of first nests (mean=8.7) was significantly larger than that of renests (mean=5.0). In one year, adults laid larger clutches than yearlings; this did not result, however, in adults' fledging larger broods than yearlings that year. Pooling years, yearling females were as successful as adults: the proportion of first nests initiated that fledged was 0.56 for yearling hens and 0.55 for adult hens. Of all the hens that settled to breed at Windy Lake in 1988 and 1989, 57% were successful in fledging a brood. Predation was the major cause of complete nest failures. Predation of clutch caused most failures (72%), followed by depredation of the hen (24%) and brood predation (4%). Cet article fait état de la phénologie de la nidification, de la biologie de la reproduction et des taux de réduction naturelle à différents stades du cycle reproducteur d'une population de lagopèdes des rochers (Lagopus mutus) à Windy Lake (Territoires du Nord-Ouest) de 1987 à 1989. Au début de mai, les mâles ...